Algerian professional football clubs during the Covid19 pandemic period - Ayad, Mostefa; Bensemicha, Laid; Brahimi , Kaddour; Kenioua, Mouloud (VIREF Revista de Educación Física, 2022)
Objective: to describe the reality of professional football clubs in Algeria during the Covid 19 pandemic period by taking the opinions of some players. Methods: the descriptive method was used; sample of the study included 30 players from the clubs’ professional championship (premium division) of the western states of Algerian football; they were chosen in an intended way, and a questionnaire was used to collect data. Results: this showed that football clubs of the professional championship in Algeria are in a deteriorating state. Conclusions: professional clubs and the National League should find solutions to the problems in sports clubs and provide capabilities and facilities in administrative matters.